New concepts to individualize calcineurin inhibitor therapy in renal allograft recipients - Sommerer, Claudia; Giese, Thomas; Meuer, Stefan; Zeier, Martin (Saudi journal of kidney diseases and transplantation, 2010)
A maximum of efficacy with a minimum of toxicity is the ultimate goal of immunosuppressive therapy. Calcineurin inhibitors are widely used as immunosuppressive drugs, and there is still a discussion about the optimal blood levels of cyclosporine A (CsA) and tacrolimus (Tac), balancing safety and efficacy. Monitoring of calcineurin inhibitor therapy is usually performed by blood trough levels, pharmacokinetics such as measurement of two hour peak levels, or by various areas under the curve assessments (AUC, 4 to 12 hours). All these mentioned pharmacokinetic measurements cannot predict the individual biological effects of the immunosuppressive drug. Several approaches have been undertaken to measure immunosuppression by calcineurin inhibitors. In this manuscript, general and specific immune monitoring strategies of calcineurin inhibitors and their clinical benefits are discussed.